A 2 shape slot microstrip patch antenna for global positioning system satellite communication applications - Md Rubel Basar; Md Al-Amin; Effat Mirza; Partha Pratim Debnath; Md Rabiul Awal (Institute of Advanced Engineering and Science, 2023)
In this paper, a compact two-shape slot microstrip antenna is proposed for global positioning system (GPS) satellite application. The proposed antenna is designed with FR 4 substrate with a height of 1.6 mm, a dielectric constant εr of 4.3 within a compact size 56 x 56 mm2 area. The design parameters are optimized to achieve good performance. At the optimum setting of design parameters, this antenna shows good characteristics to cover L1 band 1,575.42 MHz, ± 12 MHz frequency which is used for GPS satellites. At the 1,572 MHz resonance frequency, this antenna achieves a minimum return loss of -30 dB covering a frequency bandwidth of 50 MHz (1,550 MHz – 1,600 MHz) at -10 dB reference level which ensures 100% bandwidth coverage of the L1 band. Besides, the proposed antenna achieved a maximum gain of 8.3 dBi and a beam width of 1010 at -3 dB point. In terms of other performance, such as voltage standing wave ratio (VSWR), directivity, radiation pattern, the proposed antenna shows good performance for the application of GPS satellites.